Social Networks, Interpersonal Social Support, and Health Outcomes: A Health Communication Perspective - Wright, Kevin (Frontiers in Communication, 2016)
This manuscript discusses the development, impact, and several major research findings of studies in the area of social network support and health outcomes. The review focuses largely on the development of online social support networks and the ways in which they may interact with face-to-face support networks to influence physical and psychological health outcomes. The manuscript discusses this area, and it presents a research agenda for future work in this area from an Associate Editor’s perspective.